At source of nanotechnology (2014)
Nanotechnology is a broad field of modern science and also engineering, which creates, potentially, endless possibilities. This term is most often defined as the preparation and use of structures in which at least one dimension is expressed in nanometers. Usually, the dimensions of these structures are in the range from 1 to 100 nm (more often up to several hundred nm).The term nano-technology was used first time in 1974 by Japanese scientist Norio Taniguchi. He used the term to describe semiconductor processes. His definition of nano-technology was as follows: "Nano-technology mainly consists of the processing of separation, consolidation, and deformation of materials by one atom or one molecule".